At Home in Bengal: Paṭa, Paṭuā, and the Performance of Kṛṣṇa's Līlā. (24th October 2018) - Ghosh, Pika
Abstract: This brief essay explores the emergence of a distinctive regional performance of Kṛṣṇa's biography drawing from the interpolation of local themes from a rich legacy of Gauḍīya songs and temple imagery, introducing shades of nuance to popular Bhāgavata episodes. Vernacularisation, I argue, inheres no less in the interplay of the physical properties of the scroll as medium, and the ambiguities inhering in the ever-changing entanglements of visual and verbal cues, performers, and audiences. As the Bhāgavata acquires such material and performative incarnations, takes on local landscapes and tastes, and individual episodes develop lives of their own, the unmooring of specific or explicit intertextual referencing and tenuousness of linear patterns of transmission simultaneously reinforce its authority.